ROLE OF THE SEROLOGIC TEST FOR DENGUE VIRUS INFECTION - Purnama Dewi, Ni Luh Sinta; Wirawati, I.A Putri (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Dengue virus infection is infection disease cause by dengue virus. Dengue virus infection can cause a broad spectrum disease such as : dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS). Currently dengue virus ranks eighth as a cause of illness in the State of South-East Asia and Western Pacific. Epidemic dengue hemorrhagic fever (DHF) occur each year in Indonesia with a tendency incident and the affected area is increasing. Laboratory tests can be done to detect the dengue virus infection: a complete blood count and serology. Of serology test, positive IgM antibody showed that patients had a primary infection, whereas patients with secondary infections showed positive IgG antibodies, usually accompanied by antibody IgM positive. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: dengue virus infection, dengue hemorrhagic fever, serologic test